Evaluasi Sistem Pengelolaan Sumber Daya Manusia (SDM) sebagai Upaya Peningkatan Kualitas Layanan Pendidikan di PKBM Budi Utama Surabaya - Ummah, Asliatul; Yulianingsih, Wiwin (J+PLUS UNESA, 2024)
This research aims to describe the role and impact of evaluating human resource management systems in efforts to improve the quality of educational services. This type of research is descriptive with a qualitative approach. Respondents in this research were managers, tutors and students. Data collection methods include in-depth interviews, participant observation, and documentation. Data analysis consists of four stages: collection, reduction, presentation, and drawing conclusions. Data validity is confirmed through credibility, dependability, confirmability, and transferability. Source triangulation and member checks are used to ensure credibility. The results of the research show that PKBM Budi Utama Surabaya has succeeded in improving the quality of educational services by becoming an independent, well-managed and significant non-formal institution, supported by the use of the 2013 curriculum, but faced by student absences as the main obstacle.